Sea-level variation during the holocene deduced from the morphologic and stratigraphic evolution of Morgan Peninsula, Alabama, USA - Rodriguez, A. B.; Meyer, C. T. (Journal of Sedimentary Research, 2006)
Recent Gulf of Mexico shoreline studies interpret middle to late Holocene sea level as failing from a level above present elevation or stable at present elevation; however, the architecture of Morgan Peninsula, Alabama, does not support this. Morgan Peninsula is a beach-ridge strandplain composed of two obliquely aligned Holocene beach-ridge sets. Ground-penetrating radar profiles discriminate between parallel, even to wavy reflectors of the eolian dune environment and the underlying seaward-dipping, complex sigmoidal-oblique reflectors of the foreshore and upper-shoreface environment. The contact between foreshore and eolian facies in beach ridges can be used as a sea-level indicator. The average elevation of this contact in Morgan Peninsula rises throughout shoreline accretion, which occurred throughout the last 5.4 ka, suggesting that there was continual sea-level rise during this time. Morgan Peninsula is a useful modern analog to ancient shoreface-shelf parasequences and demonstrates the significant internal complexities that can exist in these deposits. Erosional discontinuities imaged in the Holocene foreshore-upper shoreface environment are laterally continuous, extend to elevations above mean sea level, and correlate to beach ridges and the transition between beach-ridge sets. An increase in the wave regime or fluctuations in sediment supply appear to be likely mechanisms for forming erosional discontinuities below beach ridges. The erosional surface separating beach-ridge sets may have formed by increased storm activity and associated barrier breaching, or a reconfiguration of the Mobile Bay tidal-delta complex superimposed on a gradual rate of sea-level rise. This boundary is recognized by a change in beach-ridge orientation at the surface and an increase in the aggradational component of shoreline accretion.
id: 2040; PT: J; UT: WOS:000235746800018